How just and just how? A systematic review of social equity in conservation research - Friedman, Rachel S.; Law, Elizabeth A.; Bennett, Nathan J.; Ives, Christopher D.; Thorn, Jessica P.R.; Wilson, Kerrie A. (IOP Publishing, 2018)
Background: Conservation decisions not only impact wildlife, habitat, and environmental health, but also human wellbeing and social justice. The inclusion of safeguards and equity considerations in the conservation field has increasingly garnered attention in international policy processes and amongst conservation practitioners. Yet, what constitutes an ‘equitable’ solution can take many forms, and how the concept is treated within conservation research is not standardized. This review explores how social equity is conceptualized and assessed in conservation research. Methods/Design: Using a structured search and screening process, we identified 138 peer-reviewed studies that addressed equity in relation to conservation actions. The authors developed a coding framework to guide the review process, focusing on the current state of, definitions used for, and means of assessing social equity in empirical conservation research. Review Results: Results show that empirical research on social equity in conservation is rapidly growing, with the majority of studies on the topic published only since 2009. Equity within conservation research is skewed toward distributional concerns and to a lesser extent procedural issues, with recognition and contextual equity receiving little attention. Studies are primarily situated in forested biomes of the Global South. Conservation interventions mostly resulted in mixed or negative impacts on equity. Synthesis and Discussion: Our results demonstrate the current limitations of research on equity in conservation, and raise challenging questions about the social impacts of conservation and how to ameliorate equity concerns. Framing of equity within conservation research would benefit from greater transparency of study motivation, more explicit definition of how equity is used within the study context, and consideration for how best to assess it.We recommend that the empirical conservation literature more deeply engage with different notions of equity when studying, planning, and implementing actions to address potential trade-offs among equity and conservation objectives and beneficiaries.